Integrative Analysis Reveals Key Circular RNA in Atrial Fibrillation - Hu, Xiaofeng; Chen, Linhui; Wu, Shaohui; Xu, Kai; Jiang, Weifeng; Qin, Mu; Zhang, Yu; Liu, Xu (Frontiers in Genetics, 2019)
Circular RNAs (circRNAs) are an emerging class of RNA species that may play a critical regulatory role in gene expression control, which can serve as diagnostic biomarkers for many diseases due to their abundant, stable, and cell- or tissue-specific expression. However, the association between circRNAs and atrial fibrillation (AF) is still not clear. In this study, we used RNA sequencing data to identify and quantify the circRNAs. Differential expression analysis of the circRNAs identified 250 up- and 126 down-regulated circRNAs in AF subjects compared with healthy donors, respectively. GO and KEGG analysis of the parental genes of the dysregulated circRNAs indicated that the up-regulated parental genes may participate in the process of DNA damage under oxidative stress. Furthermore, to annotate the dysregulated circRNAs, we constructed and merged the competing endogenous RNA (ceRNA) network and protein-protein interaction (PPI) network, respectively. In the merged network, 130 of 246 dysregulated circRNAs were successfully characterized by more than one pathway. Notably, the five circRNAs, including chr9:15474007-15490122, chr16:75445723-75448593, hsa_circ_0007256, chr12:56563313-56563992, and hsa_circ_0003533, showed the highest significance by the enrichment analysis, and four of them were enriched in cytokine-cytokine receptor interaction. These dysregulated circRNAs may mainly participate in biological processes of inflammatory response. In conclusion, the present study identified a set of dysregulated circRNAs, and characterized their potential functions, which may be associated with inflammatory responses in AF. To our knowledge, this is the first study to uncover the association between circRNAs and AF, which not only improves our understanding of the roles of circRNAs in AF, but also provides potentially functional circRNAs for AF researchers.